Severe prostate enlargement with severe lower urinary tract symptoms in poorly controlled acromegaly successfully treated with 5α‐reductase inhibitors: A 15‐year longitudinal case report. Issue 2 (5th February 2018) - Chen, Yu‐Chen; Chen, Hao‐Wei; Chen, Ming‐Tan; Huang, Chun‐Hsiung; Li, Ching‐Chia; Juan, Yung‐Shun; Ke, Hung‐Lung
Abstract : Acromegaly is a rare disease associated with an increased risk of prostate enlargement. Severe prostate enlargement with severe lower urinary tract symptoms (LUTS) in an acromegalic patient is even more uncommon. Herein we report on a 55‐year‐old man who was diagnosed with acromegaly and prostate enlargement at 40 years of age. Transsphenoidal surgery, postoperative radiotherapy, and octreotide medical therapy failed to control the acromegaly, and growth hormone (GH) and insulin‐like growth factor 1 (IGF‐1) levels remained elevated. When the patient was 53 years of age, severe LUTS and prostate enlargement (prostate volume = 128 mL) were noted. However, LUTS improved and prostate volume decreased markedly after 5α‐reductase inhibitors were used, despite the poorly controlled acromegaly (elevated GH and IGF‐1 levels). This is the first long‐term observation of LUTS and prostate enlargement in a poorly controlled acromegalic patient. Although the GH–IGF‐1 axis was a factor contributing to prostate enlargement, the present case suggests that androgens may still play an essential role in prostate enlargement and symptoms in active acromegalic patients >50 years of age. Indeed, we should be aware that suppressing the GH–IGF‐1 axis is not the only treatment choice for prostate enlargement in acromegalic patients, and even in poorly controlled acromegalic patients in whom suppression of the GH–IGF‐1 axis is difficult. Symptomatic prostate enlargement in cases of active acromegaly can be treated with 5α‐reductase inhibitors, as in general benign prostate hyperplasia populations.